2021
DOI: 10.1021/acs.joc.1c01229
|View full text |Cite
|
Sign up to set email alerts
|

Copper-Catalyzed Intermolecular C(sp2)–H Amination with Electrophilic O-Benzoyl Hydroxylamines

Abstract: A copper-catalyzed intermolecular electrophilic amination of benzamides with O-benzoyl hydroxylamines was achieved with the assistance of an 8-aminoquinolyl group. With this protocol, good compatibility was observed for a variety of aryl amides and heteroaryl amides, and excellent tolerance with various functional groups was achieved. Significantly, the monoaminated product was overwhelmingly delivered under the simple reaction conditions. Preliminary mechanistic investigations suggested that a radical pathway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…During the past decades, transition metal-catalyzed unactivated C–H bond functionalization has been the key tool for synthetic organic chemists for the site-selective construction of C–C and C-heteroatom bonds . Enormous progress has been made in chelation-assisted arene C–H activation, as compared to aldehyde C–H bond activation, which later mostly works using expensive Rh catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…During the past decades, transition metal-catalyzed unactivated C–H bond functionalization has been the key tool for synthetic organic chemists for the site-selective construction of C–C and C-heteroatom bonds . Enormous progress has been made in chelation-assisted arene C–H activation, as compared to aldehyde C–H bond activation, which later mostly works using expensive Rh catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…In such studies, we have found that N -(quinolin-8-yl)­benzamides 10 can be efficiently aminated with di- t -butyldiaziridinone ( 1 ) to provide a variety of anthranilic amides 11 (Scheme ). C–H Amination of 10 has been extensively demonstrated with Cu, Fe, Ni, Co, etc., but not with Pd. Anthranilic acid moieties are also present in various biologically and chemically significant compounds (Figure ).…”
mentioning
confidence: 99%